HUBUNGAN ANTARA KONGRUENSI GRUP PADA SUATU SEMIGRUP DENGAN HIMPUNAN BAGIAN DARI SEMIGRUP TERSEBUT YANG MEMENUHI SIFAT DENSE, FULL, TERTUTUP, E-KONJUGAT DAN KUAT-KONJUGAT - Muhammad Alfian Toni (Jurnal Matematika, 2015)
ABSTRAK. A congruence on a semigrup which classes form a group and the group hereinafter referred congruence. Semigrup subset of properties that meet dense, full, closed, E- conjugate and strong-conjugate. Given semigrup and  nonempty subsets of is said to be full if , H is said to be dense if for every  are  such that   is said to be closed if  with ,  is said to be strong-conjugate if  with  then for each ,  is said to be E-conjugate if  with  then  for each. In this thesis studied the relationship between the group on semigrup congruence with the semigrup subsets that meet the nature of dense, full, closed, E-conjugate and strong-conjugate. For each congruence group form a subset semigrup that meets the dense, full, closed, E-conjugate and strong-conjugate. And vice versa for each subset semigrup that meets the dense, full, closed, E-conjugate and strong-conjugate formed a group congruence.Kata Kunci : congruence group, dense, full, closed, E-conjugate and strong-conjugate